Produção, crescimento e marcha de absorção de nutrientes do melão cantaloupe tipo Harper fertirrigado com doses de N e K - Damasceno, Ana Paula Alves Barreto (Universidade Federal Rural do Semi-Árido, 2011)
The use of fertigation is becoming increasingly and common, however, this practice requires a thorough knowledge about the culture being used to actually be of benefit. Knowing the uptake is an important point, since this will determine how the split will occur. Among the nutrients of greatest importance to the development of crops are nitrogen (N) and potassium (K). The objective of this study was to determine growth, yield, nutritional status and the uptake for the cantaloupe melon type "Harper," conditions Mossoró-RN, in response to nitrogen and potassium. The experiment was in randomized blocks with two replications. The treatments were formed by the combination of increasing levels of nitrogen - N (N1 - 5, N2 - 37.78; N3 - 111.65; N4 - 237.65; N5 - 442.05; N6 - 666.41 kg ha-1) and potassium - K2O (K1 - 5; K2 - 82.86; K3 - 195.67; K4 - 364.61; K5 - 574.13; K6 - 827.54 kg ha-1), forming the treatments: T1 - N1K1, T2 - N2K2, T3 - N3K3, T4 - N4K4, T5 - N5K5, T6 - N6K6, being N3K3 the dose adopted by producers in the region. We evaluated the production, biomass, levels and accumulation of N, P and K in the plant. Considering all the factors studied in relation to nutrient content in the plant it was found that the treatments affected the concentration of nitrogen (N) found in the leaves at the vegetative (stem + leaves) and shoot of the whole plant and the concentration of potassium (K) in shoot of the whole plant at all sampling times, indicating that the plant responded to fertilizer application. In general, the highest values levels were found to for the treatment T5 (442 kg N and 574 kg K2O) at 44 days after transplanting (DAT). With respect to the accumulation and partitioning of dry matter and nutrients at harvest, plants receiving treatment T2 (38 kg N and 83 kg K2O) showed higher dry matter compared to other treatments, accumulated 337.8 kg ha-1 with 37% in vegetative parts (leaf + stem) and 63% in the fruit. Nutrient requirements for melon followed the order: K> N> P. To N, the highest accumulation was observed in the vegetative parts (leaf + stem), with 58.9%, while the fruit value was 41.1% for P and K, the highest accumulation was observed in fruit with 80.8% and 84.6% respectively, while in the vegetative part values were 19.2% and 15.4% respectively. The highest rate of absorption of nutrients occurred during the period around 44 days after transplanting, indicating that this is the time when the plant has increased demand for fertilizer application, since the fruits become the main drains of the plant. On treatment T3 (112 kg N and 196 kg K2O) where there is higher accumulation of nutrients, and productivity does not grow more significantly, they may be, with more further studies, this dose was used without the risk of loss due to deficiency or excess fertilizer.
Production, growth and nutrient uptake of cantaloupe melon type "Harper" fertilized with N and K
Keywords: Cucumis melo L; Plant nutrition; Uptake; Cucumis melo L; Nutrição de plantas; Marcha de absorção; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM